380. Drosophila melanogaster as a Facile Model for Large-Scale Studies of Virulence Mechanisms and Antifungal Drug Efficacy in Candida auris Candidiasis. (26th November 2018) - Bandi, Ashwini; Wurster, Sebastian; Raman, Nitya M; Albert, Nathaniel; Raad, Issam I; Beyda, Nicholas; Kontoyiannis, Dimitrios P
Abstract: Background: Candida auris is an emerging multi-drug-resistant human pathogen. Experimental data on the pathogenicity of C. auris is scarce, especially regarding its virulence compared with C. albicans . Additionally, studies of drug efficacy against C. auris rely on conventional animal models that are laborious and low throughput; alternative, less cumbersome models are desirable. To that end, we developed a C. auris fly infection model. Methods: We injected 2-week-old Toll I-RXA /Toll r632 female flies with a needle dipped in Candida solutions (10 8 yeast cells/mL) in the dorsal side of the thorax. Flies were infected with 10 different C. auris strains (source: CDC/FDA) and a C. albicans clinical strain. For drug protection studies, C. auris isolate AR-BANK#0386 [MICs: fluconazole (FLC) > 64, posaconazole (POSA) 0.125–0.25, isavuconazole (ISA) 0.25–1, voriconazole (VRC) 0.5–2 µg/mL)] was used. We assessed survival differences associated with different inocula (10 7 to 10 10 yeast cells/mL) and yeast strains. Moreover, protection conferred by addition of FLC, VRC, ISA, POSA, or FLC combined with 5-FC (flucytosine) and/or nikkomycin Z (NikZ) to fly food was studied. Three independent runs were performed for each experiment. Results: A) All C. auris strains and C. albicans exhibited comparable in vitro growth rates. B) All strains of C. auris were similarly more virulent than C. albicans ( P < 0.0001), with all flies dying by day 7 post-infection. C) FLC, VRC, ISA, FLC+5-FC, FLC+NikZ, or FLC+NikZ+5-FC-fed flies infected with C. auris #0386 had comparably poor survival outcomes compared with untreated C. auris #0386-infected flies. Interestingly, survival rates were improved in POSA-fed infected flies compared with FLC-treated or untreated infected flies ( P < 0.0001). As POSA is a cell-associated drug, we are conducting C. auris phagocytosis assays with Drosophila hemocytes that are co-incubated or not with POSA. Conclusion: Drosophila is a promising, fast, and inexpensive in-vivo model to study pathogenesis and drug activity in C. auris candidiasis. Disclosures: N. Beyda, Astellas: Scientific Advisor, Grant recipient. D. P. Kontoyiannis, Merck: Consultant, Research support and Speaker honorarium. Pfizer: Consultant, Research support. Astellas: Consultant, Research support and Speaker honorarium. Gilead: Speaker's Bureau, Speaker honorarium. F2G Inc.: Speaker's Bureau, Speaker honorarium. Cidara Inc.: Speaker's Bureau, Speaker honorarium. Jazz Pharmaceuticals: Speaker's Bureau, Speaker honorarium.